Bone mineral density: Correlation between the lumbar spine, proximal femur and radius in Northern Thai women - Namwongprom S. (2014)
Objective: To determine the correlation of bone mineral density (BMD) in lumbar spine, proximal femur and 1/3 radius in northern Thai women. Materials and Method: The data of this study was collected from the medical records and the BMD results of 885 perimenopausal and postmenopausal women who had the BMD measurement in Division of Nuclear Medicine, Department of Radiology, Faculty of Medicine, Chiang Mai University between January and December 2007. BMD was measured using dual-energy X-ray absorptiometry (Hologic, QDR-4500C). Results: Mean age (± SD) was 58.7 ± 9.9 year. The lowest T-score was found 51.6% at lumbar spine (LS), 29.2% at 1/3 radius, 13.8% at femoral neck (FN), 2.9% at total femur (TF) and 2.5% at trochanter region (TR). We found a significant correlation between age, BMI, duration of menopause, and BMD at the LS, TF, FN, TR and 1/3 radius (p < 0.01). The correlation between the BMD measures at LS and TF, FN, TR and1/3 radius were 0.708, 0.667, 0.721 and 0.633, respectively (p < 0.01). Women with perimenopausal status had higher height and BMD values at all five observed sites than postmenopausal women (p < 0.01). Conclusion: The present found a good correlation of the BMD from various skeletal sites. Interestingly, the correlation was found highest between the LS vs. TR and TF vs. TR region. Clearly, estrogen-deficient plays important role on the low BMD values in all skeletal sites.